2001
DOI: 10.1902/jop.2001.72.2.215
|View full text |Cite
|
Sign up to set email alerts
|

Collagen Membranes: A Review

Abstract: Collagen materials have been utilized in medicine and dentistry because of their proven biocompatability and capability of promoting wound healing. For guided tissue regeneration (GTR) procedures, collagen membranes have been shown to be comparable to non-absorbable membranes with regard to probing depth reduction, clinical attachment gain, and percent of bone fill. Although these membranes are absorbable, collagen membranes have been demonstrated to prevent epithelial down-growth along the root surfaces durin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
419
0
26

Year Published

2006
2006
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 466 publications
(451 citation statements)
references
References 74 publications
6
419
0
26
Order By: Relevance
“…In addition, the development of both naturally derived and synthetic materials allows the degradation properties to be controlled by the composition and ratios of compounds that comprise the material. A key advantage of this, particularly with more recently developed polymers, is that these properties can be tailored to meet the specific needs of the application with regard to how long one desires to have the material maintained [34,[41][42][43].…”
Section: Approaches For Growth Factor Deliverymentioning
confidence: 99%
“…In addition, the development of both naturally derived and synthetic materials allows the degradation properties to be controlled by the composition and ratios of compounds that comprise the material. A key advantage of this, particularly with more recently developed polymers, is that these properties can be tailored to meet the specific needs of the application with regard to how long one desires to have the material maintained [34,[41][42][43].…”
Section: Approaches For Growth Factor Deliverymentioning
confidence: 99%
“…Thus, resorbable GBR membranes are more desirable. Bovine or porcine collagen has been used as a material for resorbable GBR membranes 7,[14][15][16][17][18][19] ; however, although collagen is a highly biocompatible major matrix protein, the risk of infection with known or unknown diseases from the source animals cannot be completely eliminated, because of the physicochemically mild collagen extraction procedure [20][21][22] . An unfavorable immune reaction to the heterogeneous protein, although rare, is another concern regarding this material.…”
Section: Introductionmentioning
confidence: 99%
“…: -connective tissue maturation during the late wound healing period 10) . Other studies have also reported that, if membrane resorption occurred before 4 weeks after implantation, bone and periodontal ligament cells could not fill the space beneath the barrier membrane 29) .…”
Section: Discussionmentioning
confidence: 99%
“…Collagen membranes have been widely investigated in animal studies and human clinical studies, and have demonstrated excellent biocompatibility and cell affinity 10,11) . These membranes differ according to their tissue of origin.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation